Effect of range use on endo- and ectoparasite infestation in italian organic egg production. Issue 1 (2nd January 2019) - Lolli, Susanna; Grilli, Guido; Ferrari, Lorenzo; Ferrari, Paolo; Ferrante, Valentina
Abstract: In organic farms, hens can freely access the outdoor areas, a potential source of helminth infections. This study aimed to evaluate the effective use of free-range access in organic laying hen's farms located in Italy. The other objective was to quantify the major risk factors for endo- and ectoparasite infestation and its effect on performance, health and welfare, correlated to the use of free-range access. Fifteen organic farms of laying hens were assessed and visited twice. The total number of hens in the three zones was counted and recorded three times daily. Indirect indicators (characteristics of vegetation cover, amount and weight of droppings) were recorded. To evaluate parasite infestation, 15 fresh faecal samples per flock were collected from the ground/floor or perches. From seven farms, 15 gastrointestinal tracts from end-of-lay hens were qualitatively and quantitatively examined for the presence of endoparasites at different developmental stages. The percentage of hens observed outdoors in zone 3 was affected by free-range features. As expected, zone 1 was more frequented by hens than the others. The correlations among number and weight of droppings collected outside, vegetation score and the percentage of hens showed interesting results. Only three species of parasites were found during faecal samples analysis. There was a significantly and positively correlation between the number of Capillaria and Ascaridia eggs. The results showed that the presence in the free-range area of mounds, trees and bushes attracted more animals outside and allowed them to show their natural behaviour. Highlights: Consumer's motivations to buy organic food are related to human health, environmental concerns and animal welfare. The higher animal welfare standards of organic production lead consumers to buy organic instead of conventional food of animal origin. However, some health and welfare problems that could affect organic egg production need to be addressed. The characteristics of the outdoor range are one of the factors that can most affect its use. Moreover, the use of the free range is considered one of the major risk factors for endo- and ectoparasite infestation in organic layers that can affect performance, health and welfare.